Outcome of acute lower respiratory tract infection in infants: preliminary report of seven-year follow-up study. Issue 6338 (31st July 1982) - Mok, J Y; Simpson, H
Abstract : Seven years after admission to hospital for acute lower respiratory tract infection in infancy 200 children and their matched controls were assessed for respiratory state and epidemiological characteristics. The index group comprised 100 cases where respiratory syncytial virus infection had been responsible for the index illness (group 1) and 100 cases in whom this organism had not been found (group 2). There were no differences between index and control groups in birth weight or gestational age but fewer index cases were breast fed. Social indices such as class distribution and family size were more favourable in controls, though housing standards and maternal smoking habits were similar in the two groups. The prevalence of subsequent respiratory symptoms--cough, wheeze, nasal discharge, and hearing difficulties--was greater in index cases as was absence from school and family doctor consultation for respiratory illness. Bronchitis and asthma were significantly more common in the index group. Impaired ventilatory function and bronchial hyperreactivity were found in index cases when compared with controls. No differences in clinical characteristics and outcome were found in the two groups of index cases. The question whether lung "damage" during lower respiratory tract infection predisposes to subsequent respiratory problems or whether certain infants are more vulnerable than others to respiratory illnesses (including lower respiratory tract infection) from the onset is unanswered.